Innovation in Horticultural Practices, Enhancing Crop Quality and Marketability - Pavan Shukla; Ashutosh Singh; Amit Kumar Pandey; Akhilesh Singh (Archives of Current Research International, 2024)
This paper examines the role of innovation in enhancing crop quality and marketability in horticultural practices. It explores technological advancements, sustainable practices, and market-oriented strategies that are transforming the industry. The study covers precision agriculture, biotechnology, sustainable farming methods, and emerging technologies such as robotics and artificial intelligence. It also analyzes the impact of these innovations on crop yield, quality, and marketability, while considering environmental sustainability and economic viability. The paper concludes that continued innovation, coupled with a focus on sustainability and consumer preferences, is crucial for the future of horticulture.